2017
DOI: 10.1111/1462-2920.13660
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial communities are shaped by vegetation type and park age in cities under cold climate

Abstract: Soil microbes play a key role in controlling ecosystem functions and providing ecosystem services. Yet, microbial communities in urban green space soils remain poorly characterized. Here we compared soil microbial communities in 41 urban parks of (i) divergent plant functional types (evergreen trees, deciduous trees and lawn) and (ii) different ages (constructed 10, ∼50 and >100 years ago). These microbial communities were also compared to those in 5 control forests in southern Finland. Our results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
98
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 78 publications
11
98
3
1
Order By: Relevance
“…Contrary to previous findings (Lauber et al 2009;Hui et al 2017a), the soil microbial (PLFA) community did not correlate with pH. In contrast, the gram-/gram+ ratio did.…”
Section: Earthwormscontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous findings (Lauber et al 2009;Hui et al 2017a), the soil microbial (PLFA) community did not correlate with pH. In contrast, the gram-/gram+ ratio did.…”
Section: Earthwormscontrasting
confidence: 99%
“…Even though these two groups are not strict functional groups, they responded differently to soil pH; and in agreement with previous studies, gram-bacteria were relatively more abundant at high pH (Wang et al 2016). Further, our results also corroborate Hui et al (2017a), who showed that microbial communities (characterized with high throughput sequencing methods) in these urban parks were distinguished by plant functional types and correlated with % soil N and pH.…”
Section: Earthwormssupporting
confidence: 90%
“…Fungal community composition at 0-10 cm depth responded to plant diversity, and fungi at 11-20 cm depth responded to plant height. The contrasting responses of bacteria and fungi to conditions at different depths, and the closer association of fungal composition with changes in plant diversity, are consistent with previous findings although the driving factors are still poorly understood, ranging from pH, through nitrogen, to antecedent use (Newbound et al 2012, Xu et al 2014, Sarah et al 2015, Yan et al 2016, Hui et al 2017. In our study system, recent antecedent use is uniform across treatments suggesting that divergent effects of plant communities on soil nitrogen may contribute to differences in microbial communities.…”
Section: Soilssupporting
confidence: 90%
“…, Hui et al. ). In our study system, recent antecedent use is uniform across treatments suggesting that divergent effects of plant communities on soil nitrogen may contribute to differences in microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…, Hui et al. ). Due to their denser vegetation, forests supply an abundance of plant litter rich in lignin and cellulose, which can be degraded by Basidiomycota (Sánchez ).…”
Section: Discussionmentioning
confidence: 99%